2018
DOI: 10.1590/0102-311x00161417
|View full text |Cite
|
Sign up to set email alerts
|

Obesidade adulta nas nações: uma análise via modelos de regressão beta

Abstract: Obesity is considered a serious public health problem, as an epidemic disease with major global repercussions that is associated with the development of other chronic conditions such as hypertension, diabetes, and cardiovascular diseases. The current study examines the distribution of adult obesity in different countries using a beta regression model. This is a descriptive ecological study with a quantitative and inferential approach and a focus on beta regression analysis. Application of this method used a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
24

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 24 publications
0
10
0
24
Order By: Relevance
“…51 Chronic non-communicable diseases represent a serious public health problem, as they are pointed out as the main causes of deaths in the world, constituting a disease with great social, family and financial impact, especially for the families of affected people, since the treatments offered represent huge expenditures in the health sector. 52 However, we cannot forget all these diseases are also influenced by socioeconomic factors, difficulties in accessing health services and inadequate health care. Situations of social vulnerability and health have been related to the ethnic-racial issue, showing inequalities in the profiles of illness and death in populations that declare their skin colour like black and brown.…”
Section: Overweight In Adults (18 To 59 Years)mentioning
confidence: 99%
“…51 Chronic non-communicable diseases represent a serious public health problem, as they are pointed out as the main causes of deaths in the world, constituting a disease with great social, family and financial impact, especially for the families of affected people, since the treatments offered represent huge expenditures in the health sector. 52 However, we cannot forget all these diseases are also influenced by socioeconomic factors, difficulties in accessing health services and inadequate health care. Situations of social vulnerability and health have been related to the ethnic-racial issue, showing inequalities in the profiles of illness and death in populations that declare their skin colour like black and brown.…”
Section: Overweight In Adults (18 To 59 Years)mentioning
confidence: 99%
“…This important life stage starts when the woman is approximately 40 years old and lasts until the age of 60–65 years. It is characterized by hormonal changes and functional, morphological, psychogenic and physical modifications [ 3 ]. It is believed that, of life’s several phases, the climacteric is the one that causes the greatest impact on the woman’s health [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among different changes that affect the health of the climacteric woman, obesity occupies a prominent position. This pathology has a complex and multifactorial etiology with an epidemic character [ 5 ] and is considered a severe public health problem worldwide [ 3 ]. In Brazil, data from the Surveillance System of Risk and Protection Factors for Chronic Diseases by Telephone Survey (VIGITEL) of the year of 2017 showed that overweight was present in 50.5% of the women, increasing as age increases up to 64 years [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…S. Souza и соавт. [5] отмечают, что в 50% стран мира распространенность ожирения среди взрослых превышает 20%. Кроме того, анализ распределения распространенности ожирения по странам продемонстрировал более низкий уровень ожирения среди взрослых в странах Азии и Африки.…”
unclassified
“…Кроме того, анализ распределения распространенности ожирения по странам продемонстрировал более низкий уровень ожирения среди взрослых в странах Азии и Африки. Между тем, более высокие значения были обнаружены в странах Северной и Южной Америки и Европы [5].…”
unclassified